Mutu Madrasah: Menguji Peran Spiritualitas dan Motivasi Pendidik sebagai Mediasi Kepemimpinan Transformasional - M Nasrullah (Wahana Islamika Jurnal Studi Keislaman, 2026)
This study aims to analyze the influence of transformational leadership on the quality of Madrasah Ibtidaiyah under the auspices of LP Ma’arif NU Pekalongan Regency, with educator motivation and spirituality as mediating variables. The research method used is quantitative with a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) involving 160 respondents. Data were collected through structured questionnaires and processed using SmartPLS.The results indicate that transformational leadership, motivation, and educator spirituality have positive and significant effects on madrasah quality. Key findings reveal that transformational leadership has a dominant impact on spirituality (β = 0.748) and educator motivation (β = 0.675). Furthermore, mediation test results prove that spirituality (β  = 0.287) is a stronger mediating pathway compared to motivation (β = 0.249) in linking leadership to quality. The coefficient of determination (R2) of 0.724 indicates that this model can explain 72.4% of the variance in madrasah quality. This study concludes that transformational leadership that addresses transcendental aspects (spirituality) is the most effective strategy for boosting educational quality within the madrasah environment.